2023
DOI: 10.1002/aenm.202300188
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Dimensional Engineering in Perovskite Photovoltaics

Abstract: The low-dimensional (LD) perovskites are proven to be capable of blocking moisture erosion and thereby improving the photovoltaic device stability. In this review, the low-dimensional (LD) perovskite materials are carefully summarized that are induced by A-position organic substituents, starting from the crystal microstructure and electronic structure of LD (2D, 1D, and 0D) perovskite materials with regulating dimensions, combined with first principles calculation (DFT). By further studying the thermodynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 410 publications
0
8
0
Order By: Relevance
“…Perovskites of low dimensionality are of particular interest due to their ability to block moisture erosion and, thus, improve the stability of photovoltaic devices. 309 It was demonstrated that cautious control of the reaction conditions enabled the tuning of the material's crystallinity and, thus, their properties (i.e., electronic dimensionality and bandgaps; Fig. 37).…”
Section: Terpyridine Complexes Of Carbongroup Ions (Group 14)mentioning
confidence: 99%
“…Perovskites of low dimensionality are of particular interest due to their ability to block moisture erosion and, thus, improve the stability of photovoltaic devices. 309 It was demonstrated that cautious control of the reaction conditions enabled the tuning of the material's crystallinity and, thus, their properties (i.e., electronic dimensionality and bandgaps; Fig. 37).…”
Section: Terpyridine Complexes Of Carbongroup Ions (Group 14)mentioning
confidence: 99%
“…A variety of synthetic strategies have been developed to control the dimensionality of lead halide sublattices at the molecular level. 16 For example, incorporating organoammonium cations with large molecular size and high rigidity oen leads to the formation of low-dimensional lead halide hybrids. [17][18][19] In addition, a commonly employed approach involves varying synthesis conditions such as precursor ratios, temperatures and solvents, which oen serendipitously result in the formation of lead halide hybrids with different dimensionalities.…”
Section: Introductionmentioning
confidence: 99%
“…Key elements in the solar cell device include the perovskite active layer, the ETL, and the HTL . The PSC architecture can comprise either the standard n-i-p configuration (here referred to as a PSC), or the inverted p-i-n configuration (IPSC); the former can be further separated into mesoporous and planar structures, whereas the latter is typically planar. , IPSCs are of interest due to their advantages of lower manufacturing cost and easier integration into stacked cells with mature commercialized silicon-based solar cells. Currently, the latest inverted structure PSCs are making good progress in terms of efficiency. The efficiency development timeline of IPSCs is shown in Figure and Table .…”
Section: Introductionmentioning
confidence: 99%